APPLICATING KAPLAN-MEIER SURVIVAL ANALYSIS ON EMPLOYEE’S TENURE BY OVERTIME AVAILABILITY STATUS - Widjaya, Ferdinand Nathaniel (International Journal of Mathematics, Statistics, and Computing, 2025)
This study aimed to analyze the impact of overtime work on the tenure of employees using the Kaplan-Meier method. The data used in this research encompassed employees’ tenure records and their overtime work status in a specific company. Utilizing the Kaplan-Meier method, the analysis revealed that employees engaged in overtime work exhibited a tenure end probability higher than those who did not. The Kaplan-Meier Survival Analysis shows a much steeper step-down probability for Overtime than those who don’t. Despite the substantial disparity in tenure probabilities on the graph, furthermore, statistical analysis (log-rank test) indicated that an employee engaged in overtime work did significantly influence the duration of their tenure. These findings provide crucial insights into workload during overtime, and overtime work policies within organizations could affect the employee significantly.